1995
DOI: 10.1002/qj.49712152711
|View full text |Cite
|
Sign up to set email alerts
|

Error growth and estimates of predictability from the ECMWF forecasting system

Abstract: Examination has been made of the skill of ECMWF forecasts of the 500 hPa height field produced daily out to ten days ahead, verifying in the period from 1 December 1980 to 31 May 1994. Over this time accuracy has been improved substantially over the first half of the forecast range. The systematic (seasonal-mean) component of the error has been greatly reduced at all forecast times, but there has been little reduction in the non-systematic (transient) component later in the range.The simple model proposed by L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…As in Simmons et al (1995), Eq. (1) has been written in a discretized form, and the three parameters (α, β, γ ) have been estimated by a least-squares fit of the root-meansquare differences between consecutive forecast errors E j for j = 1,17, with t 1 = 0 and t 17 = 360 hours.…”
Section: Forecast-error Growth Model and Predictability Limitsmentioning
confidence: 98%
See 3 more Smart Citations
“…As in Simmons et al (1995), Eq. (1) has been written in a discretized form, and the three parameters (α, β, γ ) have been estimated by a least-squares fit of the root-meansquare differences between consecutive forecast errors E j for j = 1,17, with t 1 = 0 and t 17 = 360 hours.…”
Section: Forecast-error Growth Model and Predictability Limitsmentioning
confidence: 98%
“…Forecast-error growth has been studied applying the Simmons et al (1995) version of the error growth model of Dalcher and Kalnay (1987), who included in the Lorenz (1982) model both the systematic and the random error components, and nonlinear error saturation.…”
Section: Forecast-error Growth Model and Predictability Limitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The last approach "is partly dynamical and partly empirical" as noted by Lorenz (1969b) and takes errors of different scales into account (1969c). Up to now, most studies concerning the limit of predictability are based upon models (Lorenz 1965;Leith 1983;Simmons et al 1995;Mu et al 2002). Recently, several studies have shown that the limit of predictability achieved through models would depend on the calculation, the accuracy of computers and the numerical model itself (Feng et al 2001;Li et al 2000;Li et al 2001;Li et al 2006) In view of the limitations of quantifying the predictability limit by models as mentioned above, a theoretical approach based upon the nonlinear error growth dynamics was introduced.…”
Section: Introductionmentioning
confidence: 99%